The Effectiveness of Interventional Trans-Arterial Embolization to Control Active Bleeding Before Medical Treatment in Patients with Acquired Hemophilia Presenting as Retroperitoneal Hematoma and Hemothorax: A Case Report - Kim, Dong-Kyu (Journal of the Korean Society of Radiology, 2019)
The author report a case involving a 60-year-old man with acquired hemophilia who presented with sudden-onset left abdominal pain and exhibited retroperitoneal hematoma and hemothorax. In the long term, the patient is being successfully treated with recombinant activated coagulation factor VII. Before this, when the initial active bleeding was detected, successful interventional trans-arterial embolization of the lumbar arteries was performed for immediate hemostasis using N-butyl cyanoacrylate glue and microcoils. This report highlights the effectiveness of immediate interventional trans-arterial embolization in a case of active bleeding in a patient with acquired hemophilia.